Aggregation of risk indicators to cardiometabolic and musculoskeletal health in Brazilian adolescents in the periods 2008/09 and 2013/14 - Anelise R. Gaya; Arieli F. Dias; Vanilson B. Lemes; Juliana Correa Gonçalves; Priscila A. Marques; Gabriela Guedes; Caroline Brand; Adroaldo C.A. Gaya (Elsevier, 2018)
Objective: To assess the occurrence of an aggregate risk to cardiometabolic and musculoskeletal health of Brazilian adolescents in the period 2008/09 and 2013/14 and to identify whether there are differences in risk between the genders and in these periods. Methods: This was a trend epidemiological study with a quantitative approach, consisting of a voluntary sample of adolescents from 16 Brazilian states. Data were extracted from the database of Brazil Sports Project (Projeto Esporte Brasil). Health-related physical fitness was evaluated based on body mass index, cardiorespiratory fitness, flexibility, and abdominal strength/resistance. Descriptive analysis, chi-squared test, and Poisson log regression were used for the statistical treatment. Results: In the years 2008/09, 14.6% of Brazilian youngsters showed an aggregate risk to cardiometabolic health and 17.1% an aggregate risk for musculoskeletal indicators, whereas in 2013/14, the values of the risk indicators were, respectively 40.0% and 22.4%. It was observed that, in the years 2013/14, the risk to the cardiometabolic health of boys was 2.51 times greater than in 2008/09, while for girls, a three-fold increase in risk was observed. Concerning musculoskeletal health, girls showed a 2.21 risk of being in the risk zone in 2013/14 when compared with 2008/09. Conclusion: The occurrence of an aggregate risk to the cardiometabolic and musculoskeletal health of Brazilian adolescents increased in the 2008/09 and 2013/14 periods. Regarding gender, an increase in the cardiometabolic and musculoskeletal risk between these periods was observed in girls. As for boys, an increase was observed only in cardiometabolic risk. Resumo: Objetivo: Verificar a ocorrência de risco agregado à saúde cardiometabólica e musculoesquelética de adolescentes brasileiros no período de 2008/09 e 2013/14 e identificar se existem diferenças no risco entre os sexos e nesses períodos. Métodos: Trata-se de um estudo epidemiológico de tendência com abordagem quantitativa, composto por uma amostra voluntária de adolescentes, de 16 estados brasileiros. Os dados foram extraídos da base de dados do Projeto Esporte Brasil. A aptidão física relacionada a saúde foi avaliada a partir de: índice de massa corporal, aptidão cardiorrespiratória, flexibilidade, e força/resistência abdominal. Para o tratamento estatístico foi utilizado análise descritiva, qui-quadrado e regressão Poisson log. Resultados: Nos anos de 2008/09, 14,6% de jovens brasileiros apresentaram risco à saúde cardiometabólica agregada e 17,1% risco agregado dos indicadores musculoesqueléticos. Enquanto em 2013/14, os valores dos indicadores de risco foram, respectivamente 40,0% e 22,4%. Observou-se que nos anos de 2013/14 o risco à saúde cardiometabólica dos meninos era 2,51 vezes maior que em 2008/09. Já para as meninas o aumento desse risco foi de 3 vezes. No que se refere à saúde musculoesquelética, as meninas apresentaram risco de 2,21 de estar na zona de risco em 2013/14 em relação à 2008/09. Conclusão: A ocorrência de risco agregado à saúde cardiometabólica e musculoesquelética de adolescentes brasileiros aumentou no período de 2008/09 e 2013/14. Com relação ao sexo houve um aumento no risco cardiometabólico e musculoesquelético nas meninas entre esses períodos. Já para os meninos houve aumento apenas do risco cardiometabólico. Keywords: Health, Physical fitness, Obesity, Palavras-chave: Saúde, Aptidão física, Obesidade